Intracranial Inoculation Is More Potent Than Intranasal Inoculation for Inducing Optic Neuritis in the Mouse Hepatitis Virus-Induced Model of Multiple Sclerosis - Singh, Manmeet (Front Cell Infect Microbiol, 2018)
Neurotropic strains of mouse hepatitis virus (MHV) induce acute inflammation and chronic demyelination in the spinal cord and optic nerves mediated by axonal spread following intracranial inoculation in mice, with pathologic features similar to the human demyelinating disease multiple sclerosis. Spinal cord demyelination is also induced following intranasal inoculation with neurotropic MHV strains, however much higher viral doses are required as compared to intracranial inoculation. Recently, it was shown that intranasal administration of low concentrations of proteins leads to significant, rapid accumulation of protein in the optic nerve and in the eye, with only low levels reaching spinal cord and other brain regions. Thus, we examined whether intranasal inoculation with MHV at doses equivalent to those given intracranially could induce optic neuritis—inflammation, demyelination and loss of retinal ganglion cells (RGCs) in the optic nerve with or without inducing spinal cord demyelination. Four week old male C57BL/6J mice were inoculated intracranially with the recombinant demyelinating strain RSA59, or intranasally with RSA59 or the non-demyelinating strain RSMHV2 as control. One month post-inoculation, mice inoculated intracranially with RSA59 had significant myelin loss in both spinal cord and optic nerves, with significant loss of RGCs as well, consistent with prior studies. As expected, intranasal inoculation with RSA59 failed to induce demyelination in spinal cord; however, it also did not induce optic nerve demyelination. No acute inflammation was found, and no viral antigen was detected, in the optic nerve or retina 1 day after inoculation. Results confirm the neurotropic effects of RSA59 following intracranial inoculation, and suggest that direct infection with axonal transport of virus from brain to spinal cord and optic nerve is required to induce demyelinating disease. These studies suggest that MHV does not selectively concentrate in optic nerve and retina to sufficient levels to induce demyelination following intranasal inoculation. Intracranial inoculation should continue to be considered a preferred method for studies of MHV-induced optic neuritis and central nervous system (CNS) demyelinating disease.